2019
DOI: 10.3389/fphys.2019.01418
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids Modulate Systemic Metabolic Perturbation Caused by Salmonella Pullorum Challenge in Early-Stage Broilers

Abstract: The objectives of this study were to determine the protective effects of organic acids (OA) in broilers exposed to Salmonella Pullorum challenge at early stage and to explore the potential benefits of OA by metabolomics analysis. The treatment groups included non-challenged, S. Pullorum-challenged, challenged group supplemented with virginiamycin, challenged group supplemented with OA in drinking water, challenged group supplemented with OA in feed, and challenged group supplemented with OA in combination in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…The predominant gene cassette was dfrA17-aadA5 which conferring resistance to trimethoprim (dfrA) and spectinomycin (aadA) and has been reported worldwide in isolates from different origins, might be associated with the extensive use of trimethoprim and spectinomycin in broiler breeding. In addition, 61.1% class 1 integron was detected in MDR Salmonella isolates which was different the reports that all the class 1 integron exhibited resistance to at least three classes of antimicrobials [42,43].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The predominant gene cassette was dfrA17-aadA5 which conferring resistance to trimethoprim (dfrA) and spectinomycin (aadA) and has been reported worldwide in isolates from different origins, might be associated with the extensive use of trimethoprim and spectinomycin in broiler breeding. In addition, 61.1% class 1 integron was detected in MDR Salmonella isolates which was different the reports that all the class 1 integron exhibited resistance to at least three classes of antimicrobials [42,43].…”
Section: Discussioncontrasting
confidence: 91%
“…ST19 and ST 34 corresponded to S. typhimurium have contiually been reported to cause human salnellosis in resent years [44]. Another case that should be considered is ST92,a rarely reported ST which appeared in Shandong province that corresponds to S. pullorumm which often reported to cause pullorum disease of chickens in China [42].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high biological safety and beneficial functions, OA have been widely used in the field of animal feed ( Polycarpo et al, 2017 ). Previous studies indicated that the addition of OA as substitutes for AGP to the broilers’ diet obviously improved the growth performance ( Hu et al, 2019 ; Wang J. et al, 2019 ; Pham et al, 2020 ). Similarly, the positive effect of supplementation of the OA on performance was comparable to AGP in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the beneficial effects of OAs are associated with their ability to lower the pH, they may also elicit direct non-pH effects on bacterial metabolism by targeting the cell wall, and the cytoplasmic membrane, as well as function related to prokaryote replication and protein synthesis (3). Several studies reported an antimicrobial activity of OAs against most common poultry pathogens such as Clostridium perfringens (4), Salmonella (5,6), Campylobacter jejuni (7), and Escherichia coli (8). On the other hand, there are also published reports that suggest that dietary EOs may stimulate digestive secretions for enhancing nutrient digestibility (9), regulate the gut microbiota composition (10), maintain intestinal integrity, and strengthen mucosal barrier function (11), improve cellular and humoral immunity (12,13), as well as modulate the immunity related gene expression of chickens (14).…”
Section: Introductionmentioning
confidence: 99%